2003
DOI: 10.1016/s1097-2765(03)00384-8
|View full text |Cite
|
Sign up to set email alerts
|

Crosstalk between LXR and Toll-like Receptor Signaling Mediates Bacterial and Viral Antagonism of Cholesterol Metabolism

Abstract: The liver X receptors (LXR) alpha and beta are regulators of cholesterol metabolism and determinants of atherosclerosis susceptibility. Viral and bacterial pathogens have long been suspected to be modulators of atherogenesis; however, mechanisms linking innate immunity to cholesterol metabolism are poorly defined. We demonstrate here that pathogens interfere with macrophage cholesterol metabolism through inhibition of the LXR signaling pathway. Activation of Toll-like receptors (TLR) 3 and 4 by microbial ligan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

24
344
2
6

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 444 publications
(376 citation statements)
references
References 59 publications
24
344
2
6
Order By: Relevance
“…34 Moreover, recent studies revealed that the LXR signaling pathway links innate immunity to macrophage cholesterol metabolism. 50 Thus, the ability of LXRs to promote reverse cholesterol transport, attenuate inflammation, and improve glucose tolerance identifies the LXR pathway as a potential target for novel therapeutic interventions in human cardiovascular disease. 38,51,52 In the present study, we demonstrate that LXR ligands attenuate cytokine-induced CRP expression in both Hep3B cells and PHHs.…”
Section: Discussionmentioning
confidence: 99%
“…34 Moreover, recent studies revealed that the LXR signaling pathway links innate immunity to macrophage cholesterol metabolism. 50 Thus, the ability of LXRs to promote reverse cholesterol transport, attenuate inflammation, and improve glucose tolerance identifies the LXR pathway as a potential target for novel therapeutic interventions in human cardiovascular disease. 38,51,52 In the present study, we demonstrate that LXR ligands attenuate cytokine-induced CRP expression in both Hep3B cells and PHHs.…”
Section: Discussionmentioning
confidence: 99%
“…LXRs have been implicated in the regulation of cholesterol metabolism and clearance [21,22] and recently in inflammation [23,24]. Mice lacking LXR-a lose their ability to respond normally to dietary cholesterol and are unable to tolerate any amount of cholesterol in excess of that they synthesize de novo [25][26][27].…”
Section: Lipid Metabolism Of Lesion Macrophages: the Pros And Cons Fomentioning
confidence: 99%
“…In macrophages, LXR activation inhibits the expression of inflammatory cytokines (i.e. IL-1β, IL-6 and TNFα) [20,21], monocyte chemoattractant protein and osteopontin [22]. Unfortunately, first-generation LXR agonists (T0901317, GW3965) caused hypertriacylglycerolaemia through upregulation of hepatic sterol regulatory element-binding protein 1c (SREBP1c) [23].…”
Section: Introductionmentioning
confidence: 99%